KARAKTERISTIK ISLAMIC BANKING DALAM HUKUM PERBANKAN INDONESIA - Muhammad Abdul Lathif (University of Merdeka Malang, 2017)
The purpose of this study is to examine, describe and analyze holistically, comprehensively on the characteristics of Islamic Banking in Indonesian Banking Law. This research is normative juridical. The result of the research: Islamic banking has the main character that becomes the principle of Islamic Banking system in Indonesia that is the universal view that Islamic banking is applicable to every person regardless of religious difference and economic ability. Variations that the product varies from hajj and umrah savings, general savings, demand deposits, time deposits, profit sharing, buying, and selling. Facilitate that the acceptance and distribution of zakat, infaq, alms, wakaf of virtue fund have ATM facility, mobile banking, internet banking and interconnection among Islamic Banking. It is fair that Islamic banking gives something only to the right and treats something according to its portion. Maslahah Islamic banking is useful and brings virtue to all aspects of life. Transparent Islamic banking activities are very open to all people. as well as honest transactions in executing a contract/ contract. Looking at some of these characteristics, we can understand that Islamic Banking in Indonesia already has a solid initial foundation as an implementation of the Islamic Economic Philosophy.